Characterization of the leakage problem in Salhab earthen dam using electrical resistivity tomography and SP measurements, Syria - Walid AL-FARES (Contributions to Geophysics and Geodesy, 2019)
The earthen dam of Salhab is located in the southern margins of Al-Ghab plain at 3–4km of Salhab town northern-west of Syria. The dam consists of two separated embankments: the main one extends east-west along a distance of 895 m with 14.5 m height, while the second embankment towards northwest-southeast over a distance of 510 m and 11 m of height. The dam crest has a constant topographic elevation of 220 m above sea level (a.s.l). Electrical Resistivity Tomography surveys (ERT) combined with a Self-Potential measurements (SP), were implemented at the upstream and at the top of the main and the secondary embankments of the dam in order to identify the possible leakage zones under the dam’s body. The interpretation of the ERT sections and the SP measurements, carried out at the upstream side, revealed a distinct zone of leakage extending along the beginning and the end parts under the main embankment. Moreover, many punctual anomalous spots of low resistivity values were recognized within the dam’s clay core. One of those spots was confirmed by the implementation of a detailed ERT profile and by a piezometric borehole drilled at the top of the dam. Whereas, the clay core of the secondary embankment seems relatively coherent and homogeneous as well as a trace of a tectonic fault was identified under the end part of the embankment body but no manifestations of leakage were observed under and behind the secondary dam body.